Post-war transnational planning practices: Victor Gruen’s proposal for Tehran’s low-cost housing (1966-1969) - Jafari, Ellmira (International Planning History Society Proceedings, 2018)
While the communication of architectural/planning knowledge between core and periphery countries was intensified during the Cold War, it brought about new challenges regarding the relationship between imported ideas and the architectural culture of the host countries. The first master plan of Tehran, prepared by Victor Gruen and Abdolaziz Farmanfarmaian in the late-1960s, is an example of such cross-cultural dialogue, in particular with reference to the design of housing. This paper aims to examine how the first master plan introduced new low-cost housing strategy for the city of Tehran and how it affected the rapid marginalisation of the urban poor in the capital. Through a short review of the emergence of low-cost housing in Tehran since the 1940s and the examination of the two phases of the master plan, this paper seeks to unravel the complexity in the exchange of planning ideas from Western countries to Iran. In turn, the translation of Western ideas into domestic architectural vocabularies is examined through the changing local situation and the role of local mediators. The paper concludes that the privatisation of housing shifted the spotlight from state-led low-cost housing into the luxuries high-rise residential complexes which changed socio-spatial structure of the city.